Sequential Organ Failure Assessment predicts outcomes of pulse indicator contour continuous cardiac output-directed goal therapy: A prospective study. Issue 39 (September 2017) - Zhang, Wei; Danzeng, Quzhen; Feng, Xiaoting; Cao, Xing; Chen, Weiwei; Kang, Yan
Abstract : Abstract: According to the new sepsis definitions, septic shock is defined as a subset of sepsis in which the underlying circulatory and cellular/metabolic abnormalities are profound enough to substantially increase mortality. We evaluated the predictive efficacy of the Sequential Organ Failure Assessment (SOFA) score in critically ill patients with septic shock undergoing pulse indicator contour continuous cardiac output (PiCCO)-directed goal therapy (PDGT). We conducted a single-center, prospective, observational study of 52 patients with septic shock undergoing PDGT. The putative prognostic factors, including the severity scores (SOFA and Acute Physiology and Chronic Health Evaluation II [APACHE II] scores), were analyzed within 24 hours after diagnosis of septic shock. We assessed and compared the predictive efficacy of risk factors for 28-day mortality of patients with septic shock undergoing PDGT. Among the patients with septic shock undergoing PDGT, the SOFA scores of nonsurvivors were significantly higher than those of survivors ( P < .001); the area under the receiver operating characteristics curve was higher for SOFA than for APACHE II ( P = .005). The outcomes of the logistic regression analysis for 28-day mortality showed that the odds ratio, 95% confidence interval, and P -value of SOFA were 1.6, 1.2 to 2.1, and <.001, respectively. The predictive model of the SOFA score is able to accurately predict the outcomes of critically ill patients with septic shock undergoing PDGT.